Sedimentary processes and paleoenvironment reconstructions in fjords comprising the Bergsfjord peninsula, Northern Norway - Kollsgård, Christine Tømmervik (UiT Norges arktiske universitet, 2018)
Low-resolution bathymetry, high-resolution seismic data (chirp) and multi-proxy analyses of three sediment gravity cores were integrated to study sedimentary processes with the purpose of reconstructing paleoenvironments in the three north Norwegian fjords Øksfjorden, Bergsfjorden and Jøkelfjorden since the last glacial. These three fjords are located on the Bergsfjorden peninsula and surround the ice cap Øksfjordjøkelen. The multi-proxy analyses of the sediment cores included measurements of the physical properties (e.g. wet-bulk density, magnetic susceptibility), X-radiography, X-ray fluorescence (XRF) core scanning, grain-size distribution analyses and visual descriptions of the sediment cores. The results suggest that four sedimentary processes occurred in the fjords: glacier-proximal sedimentation with repeated changes of physical conditions in a glacimarine environment, suspension settling in an open-marine environment with occasional ice rafting, mass wasting, as well as deltaic processes. Furthermore, the results suggest that Bergsfjorden was deglaciated prior to c. 11,090 cal. yrs. BP and that a large-scale mass-transport event took place shortly before this time. The glacier Øksfjordjøkelen has terminated in Jøkelfjorden during the last at least 8.7 ka cal. yrs. BP. An advance of Svartfjelljøkelen and Øksfjordjøkelen occurred presumably around 8.2 ka cal. yrs. BP. Glacial activity was very reduced or absent in Bergsfjorden between 7.3 and 5.0 ka cal. yrs. BP in Bergsfjorden. Relatively steady sedimentary environments are observed after 4.2 ka cal. yrs. BP in Bergsfjorden, 5.1 ka cal. yrs. BP Øksfjorden and 5.0 ka cal. yrs. BP in Jøkelfjorden.